2017
DOI: 10.1103/physrevlett.119.167701
|View full text |Cite
|
Sign up to set email alerts
|

Insulating Josephson Junction Chains as Pinned Luttinger Liquids

Abstract: Quantum physics in one spatial dimension is remarkably rich, yet even with strong interactions and disorder, surprisingly tractable. This is due to the fact that the low-energy physics of nearly all one-dimensional systems can be cast in terms of the Luttinger liquid, a key concept that parallels that of the Fermi liquid in higher dimensions. Although there have been many theoretical proposals to use linear chains and ladders of Josephson junctions to create novel quantum phases and devices, only modest progre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
41
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 34 publications
2
41
0
Order By: Relevance
“…In a recent preprint 80 , an experimental study of the depinning in JJ chains deeply in the localized phase has been carried out. The authors have found an agreement with theoretical expectations based on the Luttingerliquid picture in the presence of disorder, which is in correspondence with our model.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…In a recent preprint 80 , an experimental study of the depinning in JJ chains deeply in the localized phase has been carried out. The authors have found an agreement with theoretical expectations based on the Luttingerliquid picture in the presence of disorder, which is in correspondence with our model.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Unexpectedly, the many-body wavefunction becomes localized at high temperatures T ≄ T M BL : T M BL ∌ E range T E J the classical dynamics of the phase is only weakly affected by the Josephson couplings and is almost periodic indicating that the system is non-ergodic in this regime. The low-temperature behavior of a related disordered system has been recently studied in the context of a Bose glass [27,28]. For numerical analysis reported here we have restricted the allowed charging states by −Q ≀ q ≀ Q with Q = 2.…”
Section: Model and Experimental Realizationmentioning
confidence: 99%
“…In the presence of disorder, such a SF ground state is generally expected to be unstable towards localization, thus forming the so-called Bose glass (BG) phase [7][8][9]: an inhomogeneous gapless compressible fluid with exponentially suppressed correlations. Disordered interacting chains can be experimentally realized using spin ladders [10,11], ultra-cold atoms [12][13][14] and arrays of disordered Josephson junctions [15][16][17]. Broadly speaking, Luttinger liquid physics is expected to occur in various contexts [18], e.g.…”
mentioning
confidence: 99%